2021
DOI: 10.1371/journal.pntd.0009475
|View full text |Cite
|
Sign up to set email alerts
|

Short Report: Adult Aedes abundance and risk of dengue transmission

Abstract: Dengue is transmitted mainly by the adult female Aedes aegypti mosquito. However, little is known about the impact of adult Aedes abundance on the risk of dengue transmission. Here we analysed nationally representative dengue case and vector surveillance data collected from Singapore, to determine the effect of adult Aedes abundance on the risk of dengue transmission. A case was an area with active dengue transmission as indicated by the presence of dengue cluster. A control was an area where no dengue cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…When using the percentage of time R t,EpiFilter > 1.0 as the dependent variable, the landed homes were associated with an increased percentage while the vegetation with structure dominated by human management (with tree canopy) was associated with a reduction in percentage (Table 4: β = -0.61%, 95% CI: -1.10%--0.11%). 1 Lags refer to the daily lagged covariate 2 Daily number of reported dengue cases 3 Daily number of reported sporadic dengue cases (i.e. Isolated cases that have no epidemiological link) 4 Daily mean absolute humidity 5 Daily mean temperature 6 Daily mean maximum temperature 7 Daily mean minimum temperature 8 Daily mean rainfall � denotes statistical significance at the 95% level https://doi.org/10.1371/journal.pcbi.1009791.t003…”
Section: Plos Computational Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…When using the percentage of time R t,EpiFilter > 1.0 as the dependent variable, the landed homes were associated with an increased percentage while the vegetation with structure dominated by human management (with tree canopy) was associated with a reduction in percentage (Table 4: β = -0.61%, 95% CI: -1.10%--0.11%). 1 Lags refer to the daily lagged covariate 2 Daily number of reported dengue cases 3 Daily number of reported sporadic dengue cases (i.e. Isolated cases that have no epidemiological link) 4 Daily mean absolute humidity 5 Daily mean temperature 6 Daily mean maximum temperature 7 Daily mean minimum temperature 8 Daily mean rainfall � denotes statistical significance at the 95% level https://doi.org/10.1371/journal.pcbi.1009791.t003…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Next, several studies have shown that Ae. aegypti abundance is associated with increased transmission [2,45,[53][54], however, due to data availability, we were unable to account for the effects of Ae. aegypti population on dengue transmissibility in our study.…”
Section: Plos Computational Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, dengue transmission is affected by a complex interplay of human, climate, mosquito, and virus. Data related to immune population status [ 47 ], population movement [ 48 ], mosquito population [ 49 , 50 ], and cycle of dengue serotypes (DENV 1–4) [ 47 ] should be further collected and used in the deep learning model to improve the prediction accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of numerous vector species in tourist areas in Botswana, including the invasive Ae. aegypti, a major contributor of dengue infections in the tropics and subtropics globally [71], highlights the need for rigorous mosquito vector surveillance in these areas. Therefore, the use of different trapping techniques in time and space may be essential in exploring a full spectrum of mosquito species diversity across varying seasonal and environmental niches [72].…”
Section: Discussionmentioning
confidence: 99%